A Web-Based Question Sharing Platform for Fostering Collaborative Learning in Higher Education - Barira Hamisu; Raji Abdullahi Egigogo; Mardiya Bagiwa; Ismail Jugulde Babaji (Yayasan Cendekiawan Digital Indonesia, 2025)
The increasing reliance on digital learning environments in higher education has not eliminated students’ difficulty in obtaining examination resources that are both academically credible and systematically organized, particularly for peer-assisted study. A web-based question-sharing platform was therefore designed and implemented to provide structured access to past examination materials within a governed collaborative environment. The platform was built using HTML, Bootstrap, PHP, and MySQL and incorporated secure authentication, role-based content management, and controlled resource sharing. System evaluation was carried out through functional testing, usability assessment, and security inspection involving undergraduate students and academic administrators; usability was captured using task completion rates and user satisfaction indicators. The evaluation documented stable system operation across core modules, high task success rates, and baseline protection against common web vulnerabilities through input validation and access restrictions. The platform also supported more consistent access to examination resources and fostered collaborative preparation practices by enabling regulated contribution and retrieval of materials. This work contributes design-oriented evidence to educational technology research by demonstrating how governance-aware architecture and usability-driven implementation can strengthen collaborative learning support without weakening assessment integrity in higher education contexts.